An Evaluation of the Workforce Investment Act Adult Program in Minnesota: Lessons from the Financial Crisis - Ellen Bendewald; Nicholas Maryns; Raymond Robertson (Institute for the Study of Labor (IZA), 2016)
Using matched administrative data, this paper estimates the program effects of Minnesota's WIA Title I-B Adult program to make two contributions to the literature. First, this paper applies a wide range of non-experimental approaches and generates similar estimates of program effects that are consistently larger than most other evaluations. Second, comparing workers job seeking in 2007-2008 with those job seeking in 2009-2010 suggests that the workers job seeking in a growing job market experience more persistent program effects.
Keywords: J28; J38; J68; 330; pseudo-experimental; job training; WIA-Adult